KEMAMPUAN PENGENDALIAN JUMLAH BAKTERI PADA TANGAN DAN STABILITAS FISIK GEL HAND SANITIZER EKSTRAK ETANOL 96% KULIT BUAH PISANG AMBON (Musa parasidiaca) - siti nur azizah; Septia Nurcahyaningsih; Agnis Agnis Pondineka Ria; Amaliyah Nurul Hidayah (BIOSAPPHIRE: Jurnal Biologi dan Diversitas, 2023)
The purpose of this study was to determine the physical stability of hand sanitizer gel 96% ethanol extract of Ambon banana peel (Musa paradisiaca) and the ability to control the number of bacteria on the hands. The formulation is carbopol 940, HPMC, TEA, Methylparaben, and Ambon banana peel extract (Musa paradisiaca). Tests for hand sanitizer gel preparations include organoleptic tests, dispersibility, homogeneity, pH, viscosity, skin irritation, and controlling the number of bacteria on the hands. The results of the organoleptic physical stability test on day 0 and day 30 affected texture and color but did not affect aroma. The dispersion test on day 0 was 6.53 and on day 30 it was 6.26. The homogeneity test on day 0 and day 30 is homogeneous. The pH test on day 0 was 5.96 and on day 30 it was 5.83. The viscosity test on day 0 is 2,900 and on day 30 is 2,900. Test the percentage of the number of bacteria on the hands before and after day 0 the results of R1 were 6,4% R2 75% R3 87,8%. And on day 30 the result is R1 91,4% R2 76,19% R3 97,05%. Based on the results, it can be concluded that the 30-day real-time physical properties stability test met the requirements of the gel preparation. Bacterial control test on the respondent's hands before and after using hand sanitizer gel of Ambon banana peel extract was able to reduce the percentage of bacteria on each respondent's hand.